Post-communist transformation: methodological issues - Buivydas, Skirmantas (Politologija, 1999)
Motivated by the lack of conceptually disciplined studies of post-communist transformation characteristic to the discipline of political science in Lithuania, the author expresses the purpose of the article as follows—to join and try to contribute to the development of theoretical discussions of post-communist transformation. Herein, the author defines the concept of Central Europe as embracing the Visegrad states (Czech Republic, Slovakia, Poland, Hungary) and Lithuania.In this article, the author undertakes to research the dilemma concerning the application of theoretical instruments of democratization for the analysis of post-communist political change (transformation). Herein, the research is directed to explore the following issue: are the theoretical schemes for the analysis of non-democratic regimes applicable to explain the post-communist transformation, or should the new theories assessing the specifics of post-communist transformation be developed, otherwise? Hence, the author presents two methodological approaches—procedural and structural—used to explain the phenomenon of political change; similarly, in the context of post-communist transformation, the author ponders upon their productivity, reflects on the question whether post-communist democratization provides for clarification of comparative political research methodologies. Mr. Buivydas refers to such prominent scientists like P. Schmitter (democratization of authoritarian political regimes), G. Sartori (issue of "conceptual stretching" in studies of democratization), Collier and Levitsky (conceptual innovations in comparative research, definitions of democracy), Schumpeter, R. Bova (analysis of issues arising from conceptual stretching, three-level analysis to elucidate conceptual differences between countries which underwent democratization of non-communist authoritarianism and post-communist transformation), and others.He accentuates the constructive role of Melvil's "causal filter" scheme to analyze the second phase of political transformation—democratic consolidation.The author comes to admit that the process of post-communist change in Central East Europe stirs the efforts to clarify the methodology of political research as an activity. The third wave of democracy, as well as the evolution of communist states to democracy, stipulates one to renounce the aged methodological dichotomy apparent between structural and procedural explanations for political regime change. Neither of these methodologies, however, when apart from the other, is able to explain both the genesis of democratic transformations in the 80s and 90s and the further developments the political process of the new democracies has faced. The former and the latter seem particularly obvious in the case of post-communist transformation, where the mosaic of internal peculiarities and political strategies disclaim deterministic arguments, let alone laterally directed ones. Thus, in order to get a full picture of the logic of democratic change in Central East Europe, one must integrate both structural and procedural approaches as well as take account of the impact the institutional and international contexts exert. Such a theoretical-methodological synthesis gives priority to procedural factors during the phase of transformation into democracy, whereas structural factors serve as stimuli initiating the regime change and stabilizing the political process. Integrated theory of democratization, constructed on the basis of post-communist change, is entitled to transmit a weighty contribution into the studies of transition.On the other hand, preliminary evaluation of the success of the democratic project in Central East Europe is driven but by the meaning various authors attach to the very concept of democracy. The concept of democracy is immensely capacious; it covers a wide range of explanations—starting from minimalist and ending up with socio-culturally orientated definitions. Aware of that, several analysts of post-communism express their doubts as to the democratic nature of political change in the region. To avoid theoretical cul-de-sac, it seems viable to differentiate post-communist space and agree upon common attributes of the phenomenon referred to as democracy. Minimalistic concept of democracy is still most easily operationalized and verified. However, comparative political research, given that correct criteria of its content are outlined, can refer to more complex conceptions of democracy.
Keywords: -